Literature Review: Kejadian Hipotensi pada Pasien yang Menjalani Tindakan Anestesi Spinal - Raihannisa Anjani; Zaki Fikran (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Spinal anesthesia is one of the regional anesthesia methods that is often chosen in various surgical procedures, especially in the area of the lower extremities, pelvis, and lower abdomen. The most common complication encountered in this technique is the occurrence of hypotension, which can affect tissue perfusion and hemodynamic stability of the patient. This study aims to examine the incidence of hypotension in spinal anesthesia, including mechanisms, risk factors, and management. The method used in this study is literature review with a scientific source search process conducted through various databases PUBMED, Sciencedirect, Researchgate, and Google Scholar with a publication year range of 2016 to 2026. The results showed that hypotension arises as a consequence of an obstacle in the sympathetic nervous system, which provokes dilation of blood vessels as well as reduced venous return. Risk factors include age, body mass index, patient position, block height, duration of surgery, fluid status, Injection Point, and type of anesthetic drug used. Management is carried out by administering fluids, vasopressors, as well as strict hemodynamic monitoring. A good understanding of the risk factors and mechanisms of hypotension is expected to improve patient safety during spinal anesthesia..